Indonesian Societas Verbi Divini (SVD) Missionaries in the Netherlands - Fransiska Widyawati (Institut Kristen Teologi Real Batam, 2026)
This article examines the deployment of Indonesian Societas Verbi Divini (SVD) missionaries to the Netherlands as a structured expression of